Impacts of Early‐ and Late‐Terminated Cover Crops on Gas Fluxes. Issue 6 (1st November 2018) - Ruis, Sabrina J.; Blanco‐Canqui, Humberto; Jasa, Paul J.; Ferguson, Richard B.; Slater, Glen
Abstract : Cover crops (CCs) could alter soil processes, but the effects of early versus late termination of CCs on gas fluxes are not well known. We evaluated temporal changes in fluxes of CO2, N2 O, and CH4 and related soil properties in no‐till corn ( Zea mays L.) with and without winter rye ( Secale cereale L.) CCs that were terminated early (30 d before planting) or late (at planting) in a rainfed silty clay loam and an irrigated silt loam in Nebraska from April 2016 to June 2017. Gas fluxes, soil temperature, and soil water content were measured biweekly to monthly, and wet aggregate stability and particulate organic matter concentrations were measured seasonally. We also compared our results with a global literature review. Late‐terminated CCs did not affect CH4 fluxes but increased daily CO2 fluxes by 59% compared with no CC at both sites and N2 O fluxes by 92% at the rainfed site only. Early termination did not affect gas fluxes. Termination date did not affect cumulative fluxes and had minimal effects on soil properties. The literature review supports our study results, which indicate that CC effects on (i) CO2 fluxes are driven by plant respiration during the CC growing period, and (ii) N2 O and CH4 fluxes are minimal under grass CCs. Overall, under no‐till, CC termination date has small effects on N2 O and CH4 fluxes, but late CC termination can increase CO2 fluxes in spring due to greater biomass yield compared with early termination. Core Ideas: Early‐terminated cover crops had limited effects on CO2 fluxes in this study. Late‐terminated cover crops increased CO2 flux mainly in spring due to higher cover crop biomass yield. Cover crop termination effects on N2 O and CH4 fluxes were generally nonsignificant. Our literature review showed cover crops affected CO2 mostly during their growing period. Our literature results also showed grass cover crops had limited effects on N2 O.